Aspectos laborales en la ley de libertad religiosa y su reglamento - Ulloa, Daniel (2012)
Labor Issues in the religious freedom act and its regulationThis text reviews the constitutional and legal regulation of religious freedom, considering the definition of its content established by the Constitutional Court and its application in the labor contracts, both common and those involving an ideological employer or with ideological trend